Copper-Catalyzed Synthesis of N-Heterocyclic Compounds - Liu, Tao; Fu, Hua (Synthesis, 2012)
The synthesis of N-heterocyclic compounds is an important direction because of their diverse biological functions. Recently, there has been remarkable progress in copper-catalyzed cross couplings with inexpensive, readily available, insensitive-to-air and low-toxicity copper catalysts. This review summarizes recent advances in the copper-catalyzed synthesis of N-heterocyclic compounds.1 Introduction and Background2 Synthesis of Five-Membered Heterocycles with One Nitrogen Atom2.1 Pyrrolidine and Pyrrole Derivatives2.2 Indole Derivatives2.3 Indolone and Isoindolone Derivatives2.4 Oxazole, Isoxazole, Benzoxazole and Benzothiazole Derivatives3 Synthesis of Five-Membered Heterocycles with Two Nitrogen Atoms3.1 Imidazole Derivatives3.2 Benzimidazole Derivatives3.3 Benzimidazolone Derivatives4 Synthesis of N-Sulfonyltriazoles5 Synthesis of Six-Membered Heterocycles with One Nitrogen Atom5.1 Piperidine and Pyridine Derivatives5.2 Quinoline and Quinolinone Derivatives5.3 Isoquinoline Derivatives6 Synthesis of Six-Membered Heterocycles with Two Nitrogen Atoms6.1 Quinazoline Derivatives6.2 Quinazolinone Derivatives7 Synthesis of N-Fused Heterocycles8 Summary
Keywords: copper catalysis; N-heterocyclic compound; five-membered heterocycle; six-membered heterocycle; N-fused heterocycle